HUBUNGAN SELF AWARENESS DENGAN PERENCANAAN KARIR PESERTA DIDIK DI KELAS XII SMK SEMEN PADANG - fikra adila; Weni Yulastri; Besti Nora Dwi Putri (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This research is motivated by the existence of students who have not planned their careers after graduating from SMK. The research aims to: 1) Describe the self awareness of the XII grade students of SMK Semen Padang. 2) Describe the career planning of the students of SMK Semen Padang. 3) To see the relationship between self awareness and career planning. This type of research is descriptive quantitative correlation. The population of this study was the students of SMK Semen Padang as many as 97 students. The sampling technique was carried out by total sampling, that is, all of the population was sampled, amounting to 97 people. The instrument used in this study is a questionnaire, data analysis techniques using the Pearson Product Moment Correlation formula using the SPSS version 22 application. The results of research on student career planning are in the high category. Self awareness of students is in the very high category. The data analysis categories obtained the following results: There is a significant positive relationship between self awareness and career planning of students with a correlation or rcount of 0.273 and rtable of 0.2 df 95 at a significance level of 0.05 or a 95% confidence level. rcount rtable, it can be concluded that the working hypothesis (Ha) is accepted and there is a significant relationship between self awareness and students' career planning. For this reason, it is recommended that BK teacher education provide counseling services related to increasing self-awareness and career planning, which is specifically for students who are in the medium and low categories to become high